Development of Learning Media Volleyball Materials - Hasibuan, Muhammad Alwi Fahrozi; Khairul Usman (Educational Sciences Journal, 2024)
This study aims to obtain a product for developing volleyball learning media for class VIII students of SMP Negeri 1 Aek Natas. The research was carried out to facilitate learning in the volleyball material network with the product results in the form of videos and assessed by experts and student trials during the Covid-19 pandemic. The formulation of the problem in research. This research uses research and development (RnD) method. The research was conducted to develop a form or a learning media for soccer material that was applied at the elementary school level. The research was conducted by applying the Thiagarajan theory using research and development steps with 4 D, namely define, design, development, and dissemination. The research data source aims to collect data from the stages of product development. The data obtained comes from two parts, namely primary data and secondary data. Data collection techniques are carried out through the product development stages. The product development stage is carried out with the results of the FGD of experts related to the development of volleyball video products. The results showed that product development for learning was declared feasible (accepted) by volleyball experts and information and technology (IT) experts. The product development stage was then tested and with the results of the FGD of the experts related to the development of video-based media products. The results obtained from the entire series of product trials are in the good category, namely the product is suitable for use as a learning medium for class VIII students of SMP Negeri 1 Aek Natas. The stage of obtaining video feasibility data can be applied as a research product during the covid-19 pandemic. The conclusion in this study is the development of video-based learning media on volleyball material for class VIII SMP Negeri 1 Aek Natas was developed with MP4 format that can be played on video applications, namely VLC and Windows Media Player. The video product is a reference for PJOK learning during the COVID-19 pandemic, volleyball material. Products that are followed up will result in improvements towards superior products in Junior High School PJOK learning. It is recommended that the product is very necessary to do follow-up research at the testing stage to produce a product that is more in line with the development process.